Identifying Paucisymptomatic or Asymptomatic and Unrecognized Ebola Virus Disease Among Close Contacts Based on Exposure Risk Assessments and Screening Algorithms. (1st September 2022) - Gayedyu-Dennis, Dehkontee; Fallah, Mosoka P; Drew, Clara; Badio, Moses; Moses, J S; Fayiah, Tamba; Johnson, Kumblytee; Richardson, Eugene T; Weiser, Sheri D; Porco, Travis C; Martin, Jeffrey N; Sneller, Michael C; et al.
Abstract: Background: There is limited evidence to evaluate screening algorithms with rapid antigen testing and exposure assessments as identification strategies for paucisymptomatic or asymptomatic Ebola virus (EBOV) infection and unrecognized EBOV disease (EVD). Methods: We used serostatus and self-reported postexposure symptoms from a cohort study to classify contact-participants as having no infection, paucisymptomatic or asymptomatic infection, or unrecognized EVD. Exposure risk was categorized as low, intermediate, or high. We created hypothetical scenarios to evaluate the World Health Organization (WHO) case definition with or without rapid diagnostic testing (RDT) or exposure assessments. Results: This analysis included 990 EVD survivors and 1909 contacts, of whom 115 (6%) had paucisymptomatic or asymptomatic EBOV infection, 107 (6%) had unrecognized EVD, and 1687 (88%) were uninfected. High-risk exposures were drivers of unrecognized EVD (adjusted odds ratio, 3.5 [95% confidence interval, 2.4–4.9]). To identify contacts with unrecognized EVD who test negative by the WHO case definition, the sensitivity was 96% with RDT (95% confidence interval, 91%–99%), 87% with high-risk exposure (82%–92%), and 97% with intermediate- to high-risk exposures (93%–99%). The proportion of false-positives was 2% with RDT and 53%–93% with intermediate- and/or high-risk exposures. Conclusion: We demonstrated the utility and trade-offs of sequential screening algorithms with RDT or exposure risk assessments as identification strategies for contacts with unrecognized EVD. Abstract : In this cohort, we created hypothetical scenarios demonstrating that symptomatic individuals who test negative for Ebola virus by World Health Organization case definition would benefit more from sequential screening algorithms with rapid diagnostic testing than those with exposure risk assessments.